Camped in Otherness: The Role of Nature at Music Festivals. - Green, Ryan A (2016)
Market growth within the festival industry has lead to a burgeoning body of research in the area, largely focused on consumer motivations or the social, economic or environmental impact of these events. As supply and demand both continue to increase, the quest for authenticity among attendees has been matched by a growing industry focus in the role of the festival site as differentiation. By building on the theory of festival tourism as a process of ‘Otherness’, this thesis analyses the experiential role of nature within these encounters. Through semi-structured interviews carried out at two UK based festivals, conversational analysis is used to interpret consumer narrative assemblages of otherness. By drawing on nature tourism and experiential consumer research, these narratives are examined through their formulation, categorisation, tensions, and outcomes, in order to consider what the role of nature is within these assemblages. The paper finds that although consumer’s relationships and experiences with nature are individual and quixotic, subsequent tensions are raised by consumer ideologies, which have consequential impacts on festival experience, the wider festival market, and their socio-cultural importance.